Wake of Death: Using historical and contemporaneous data to evaluate the Isopisthus parvipinnis (Sciaenidae) population structure at the Southwest Atlantic Ocean (23º - 26.9ºS) - Hoff, Natasha Travenisk (2021)
This thesis aimed to answer three questions about the population structure of Isopisthus parvipinnis along the southern area of its distribution in the Southwest Atlantic Ocean (23ºS - 26.9ºS): - if there are phenotypic population units of the species; - whether there is spatial and temporal maintenance of the population structure; - and whether natural markers such as body morphometry, otolith morphometry-shape and chemical composition of otolith can identify these phenotypic differences. The individuals of I. parvipinnis (between 66 - 139 mm in total length) were collected in September and November 1975 (Nectonic Fauna Project - FAUNEC) and between September 2018 and May 2019, by commercial and scientific fishing. The morphometric body analysis was applied only to contemporary data, while the form indexes (SIs), the Fourier elliptic descriptors (EFDs) and the analysis of the chemical composition of the post-total dissolution otoliths were applied to both periods. The statistical analysis detected variations for all natural tags, concerning the locations (São Paulo: north - NSP, center - CSP, and south - SSP; Paraná - PR; Santa Catarina - SC) and the collection periods. All body morphometric distances presented significant differences among locations, while EFDs responded better to spatial and temporal variations than SIs. At least eight elementary ratios showed significant differences between the localities in both periods. The results suggest changes in the population structure of I. parvipinnis from one or two population units in 1975 to at least four population units in 2018/2019 (NSP, CSP, SSP / PR, SC), depending on the adopted method, as a response to the different oceanographic characteristics of the study area, feeding patterns, anthropogenic influences, pollution, and climate change. Besides, there was an improvement in the reclassification of individuals to their place of origin: 79% by body morphometry, from 42 to 81% by otolith morphometry and from 58 to 80% by otolith chemical composition for both periods (1975, 2018/2019).